2020
DOI: 10.1016/j.ribaf.2020.101293
|View full text |Cite
|
Sign up to set email alerts
|

The role of internal corporate governance mechanisms on default risk: A systematic review for different institutional settings

Abstract: Recent financial downturns, characterized by the significant failures of firms, have revealed the need to control credit risk. Latest literature has shown that weak corporate governance structures are related to high levels of default risk, leading to financial instability. In this context, we aim to summarize the literature that focuses on the role that internal corporate governance plays in the credit risk of firms, specifically considering three corporate governance components: ownership structure, board st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 125 publications
0
31
0
Order By: Relevance
“…The literature review indicates, in line with political cost and resource dependence theories, not only a statistically significant and positive nexus between compliance with stakeholder Corporate Governance provisions and financial performance (Beiner et al, 2006;Ntim, 2013), but also the existence of internal (Ballester et al, 2020;Hongxing & Yuna, 2013;Kamardin & Haron, 2011;Martínez-Ferrero & García-Meca, 2020) and external (Aguilera et al, 2015;Fan & Wong, 2005;Jacoby et al, 2019;Shi et al, 2017) governance mechanisms that can be classified in a framework. Interestingly, external mechanisms of corporate governance were observed to be legal system, corporate control, external auditing and rating organizations (Gao & Kling, 2012).…”
Section: Resultsmentioning
confidence: 80%
“…The literature review indicates, in line with political cost and resource dependence theories, not only a statistically significant and positive nexus between compliance with stakeholder Corporate Governance provisions and financial performance (Beiner et al, 2006;Ntim, 2013), but also the existence of internal (Ballester et al, 2020;Hongxing & Yuna, 2013;Kamardin & Haron, 2011;Martínez-Ferrero & García-Meca, 2020) and external (Aguilera et al, 2015;Fan & Wong, 2005;Jacoby et al, 2019;Shi et al, 2017) governance mechanisms that can be classified in a framework. Interestingly, external mechanisms of corporate governance were observed to be legal system, corporate control, external auditing and rating organizations (Gao & Kling, 2012).…”
Section: Resultsmentioning
confidence: 80%
“…They analyzed the social, cultural, psychological, political, and law compliance aspects to reveal the behavioral determinants of NPLs. Again, Ballester et al (2020) conducted a systematic literature survey that focused on corporate governance mechanism on NPLs such as ownership, board structure, and financial stakeholders' rights and relations. They found that a large extent of default risk is originated from the weak corporate governance structures of bank.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In particular, we analyse the association that relates banks' risks of default to characteristics of corporate governance in terms of size, independence, the duality of the Chief Executive Officer (CEO) and gender diversity. These board components have been identified by the previous literature, both at a theoretical and empirical level, as determinants of company credit risk (see Ballester et al (2020) and Fernandes et al (2018) for a full compilation of the scarce research on the relationship between board characteristics and bank failures). The default risk measure we employ is Merton's (1974) distance to default (DD) measure.…”
Section: Introductionmentioning
confidence: 97%